What Drives Students of Vocational Training Program? An Investigation on the Significance of Foreign Language Acquisition - Solodkova, Irina M.; Grigorieva, Elena V.; Ismagilova, Liliya R.; Polyakova, Oksana V. (Journal of History Culture and Art Research, 2017)
The paper dwells on the distinguishing the motives that drive students of vocational training program in terms of foreign language acquisition being the main component of future employment success. In fast-changing world which is teemed with new challenges and career patterns foreign language acquisition is viewed as a foremost aspects of promotion. The aim of the current study was to identify the main motives that drive students of vocational training program for foreign language acquisition and later equip higher education authorities and teaching staff with the data to improve language education complying with the students’ requirements. To find out internal and external motives of the students enrolled to the program at The Educational Center for Professional Communicative Training of Kazan Federal University a questionnaire survey was organized. The results of the research identify that there are differences in students’ priorities of external and internal motives and there is a prevalence of the internal ones. It is accounted for by the fact that students of the program realize the significance of foreign language acquisition for their personal needs and future professional activity. But practically all of them emphasized the same personal and interpersonal factors of internal motivation. The obtained findings will be exploited as recommendations in designing the syllabus and will be of great help in choosing the appropriate forms and techniques in carrying out the course.